Wireless sensor network with energy harvesting: modeling and simulation based on a practical architecture using real radiation levels. (9th October 2013) - Climent, S.; Sanchez, A.; Blanc, S.; Capella, J. V.; Ors, R.
Summary: This paper presents a new energy‐harvesting model for a network simulator that implements super‐capacitor energy storage with solar energy‐harvesting recharge. The model is easily extensible, and other energy‐harvesting systems, or different energy storages, can be further developed. Moreover, code can be conveniently reused as the implementation is entirely uncoupled from the radio and node models. Real radiation data are obtained from available online databases in order to dynamically calculate super‐capacitor charge and discharge. Such novelty enables the evaluation of energy evolution on a network of sensor nodes at various physical world locations and during different seasons. The model is validated against a real and fully working prototype, and good result correlation is shown. Furthermore, various experiments using the ns‐3 simulator were conducted, demonstrating the utility of the model in assisting the research and development of the deployment of everlasting wireless sensor networks. Copyright © 2013 John Wiley & Sons, Ltd.